Upper-Extremity Dual-Task Function: An Innovative Method to Assess Cognitive Impairment in Older Adults - Toosizadeh, Nima; Najafi, Bijan; Reiman, Eric M.; Mager, Reine M.; Veldhuizen, Jaimeson K.; O’Connor, Kathy; Zamrini, Edward; Mohler, Jane (Frontiers in Aging Neuroscience, 2016)
Background: Difficulties in orchestrating simultaneous tasks (i.e., dual-tasking) have been associated with cognitive impairments in older adults. Gait tests have been commonly used as the motor task component for dual-task assessments; however, many older adults have mobility impairments or there is a lack of space in busy clinical settings. We assessed an upper-extremity functional (UEF) test as an alternative motor task to study the dual-task motor performance in older adults. Methods: Older adults (≥ 65 years) were recruited, and cognitive ability was measured using the Montreal cognitive assessment (MoCA). Participants performed repetitive elbow flexion with their maximum pace, once single-task, and once while counting backward by one (dual-task). Single- and dual-task gait tests were also performed with normal speed. Three-dimensional kinematics were measured both from upper-extremity and lower-extremity using wearable sensors to determine UEF and gait parameters. Parameters were compared for the cognitively impaired and healthy groups using analysis of variance tests, while controlling for age, gender, and body mass index (BMI). Correlations between UEF and gait parameters for dual-task and dual-task cost were assessed using linear regression models. Results: Sixty-seven older adults were recruited (age=83±10 years). Based on MoCA, 10 (15%) were cognitively impaired. While no significant differences were observed in the single-task condition, within the dual-task condition, the cognitively impaired group showed significantly less arm flexion speed (62%, d=1.51, p=0.02) and range of motion (27%, d=0.93, p=0.04), and higher speed variability (88%, d=1.82, p<0.0001) compared to the cognitively intact group, when adjusted with age, gender, and BMI. Significant correlations were observed between UEF speed parameters and gait stride velocity for dual-task condition (r=0.55, p<0.0001) and dual-task cost (r=0.28, p=0.03). Conclusion: We introduced a novel test for assessing dual-task performance in older adults that lasts 20 seconds and is based on upper-extremity function. Our results confirm significant associations between upper-extremity speed, range of motion, and speed variability with both the MoCA score and the gait performance within the dual-task condition.